ANALISIS USAHATANI DAN PEMASARAN TOMAT (Lycopersicon escelentum Mill) DI DESA TESBATAN, KECAMATAN AMARASI, KABUPATEN KUPANG - Marcelita Asriani; Marthen Robinson Pellokila; Selfius P. N. Nainiti (Undana Press, 2021)
This study aims to: 1) Knowing the condition of Tomato farming in Tesbatan Village, 2) Knowing the Tomato marketing pattern in Tesbatan Village, 3) Knowing the amount of income, profit, farmer share, and marketing margin received by Tomato farmers in Tesbatan Village, 4) Knowing the efficiency level of Tomato marketing in Tesbatan Village. The method used in this research is quantitative descriptive analysis. The results showed that: 1). The farming condition in Tesbatan Village is very advanced, where it fills good tomato cultivation methods, and uses certified seeds. 2). There are two patterns of tomato marketing carried out by farmers in Tesbatan Village, namely: a). farmers sell directly to last consumers, b). farmers sell their crops to retailers and then to last consumers. 3). The amount of farm income received by farmers in Tesbatan Village in 2019 is Rp. 670,696,500 with an average income per respondent farmer of Rp. 17,649,908; The farmer's share value in the Tomato marketing channel in Tesbatan Village, in the first marketing channel was 100, while in the second marketing was 75; as well as the marketing margin of Tomatoes in Tesbatan Village, Amarasi District, Kupang Regency, namely Rp. 5000. 3). Tomato farming and marketing in Tesbatan Village is very efficient because it has a value of less than 1.